Feasibility of double sleeve lobectomy after neoadjuvant chemotherapy in patients with non-small-cell lung cancer. (21st April 2022) - Bao, Yi; Jiang, Chao; Wan, Ziwei; Wang, Yang; Zhong, Yifan; Deng, Jiajun; She, Yunlang; Jiang, Lei; Hu, Xuefei; Zhu, Yuming; Yu, Bentong; Chen, Chang
Abstract: OBJECTIVES: This study intends to appraise the feasibility of double sleeve lobectomy after neoadjuvant chemotherapy in central non-small-cell lung cancer with bronchovascular aggression. METHODS: This retrospective study included non-small-cell lung cancer patients who received double sleeve lobectomy from January 2014 to June 2020. Patients were divided into 2 groups: the neoadjuvant chemotherapy group and the non-neoadjuvant chemotherapy group. Demographic data and perioperative outcomes were compared between these 2 groups. RESULTS: Of the 110 patients who received double sleeve lobectomy during this period, 35 patients (31.8%) received neoadjuvant chemotherapy. Compared with the non-neoadjuvant chemotherapy group, patients who received neoadjuvant chemotherapy were associated with younger age ( P  = 0.026), smaller pathologic tumour size ( P  = 0.005), higher forced expiratory volume in 1 s ( P  = 0.007), higher forced expiratory volume in 1 s of predicted value ( P  = 0.005) and higher clinical stage ( P  < 0.001). In the neoadjuvant chemotherapy group, 18 patients (51.4%) attained a partial response and 17 patients (48.6%) achieved stable disease. The postoperative hospital stays ( P  = 0.042) and chest tube drainage duration ( P  = 0.030) were longer in the neoadjuvant chemotherapy group and other perioperative performances were similar between these 2 groups. No statistically significant difference was reported in postoperative complications and mortality between these 2 groups. CONCLUSIONS: The intraoperative performance and postoperative outcomes of double sleeve lobectomy following neoadjuvant chemotherapy were similar to direct surgery, indicating that double sleeve lobectomy after neoadjuvant chemotherapy is feasible and safe in central lung cancer involving both the pulmonary artery and bronchus. Abstract : Lung cancer is the second most common malignancy worldwide, with non-small cell lung cancer (NSCLC) accounting for over 85% of all cases [1, 2].